BaZrO3 based non enzymatic single component single step ceramic electrochemical sensor for the picomolar detection of dopamine. Issue 5 (1st March 2022) - Thomas, Jasmine; Anitha, P.K.; Thomas, Tony; Thomas, Nygil
Abstract: BaZrO3 perovskite crystallites were synthesized in a single step using a calcination free room temperature co precipitation method. Crystallite size, presence of metal oxygen bond, thermal stability, defect structure, surface morphology were studied using structural, thermal and microscopic investigations. This material was used for the modification of carbon paste electrode (CPE) for the fabrication of an advanced sensor. The modified electrode exhibited lower resistance and better charge transfer compared to an unmodified electrode. The electrochemical characteristics investigated using CV and DPV showed high current sensitivity towards the detection of dopamine (DA). The modified electrode achieved a remarkable low concentration of 5 pM detection limit level for the detection of DA. Limit of detection for co existing molecules of uric acid (UA) and ascorbic acid (AA) were 500 pM and 500 nM respectively. The developed sensor could quantify the DA in the presence of uric acid (UA) and ascorbic acid (AA). Mixed sample analysis, interference studies, stability analysis etc prove the competence of the developed sensor. Real sample analysis in blood plasma and urine marked the practical utility of the developed sensor. Graphical abstract: Image 1